ANALISIS VOLATILITAS HARGA DAGING SAPI POTONG DAN DAGING AYAM BROILER DI INDONESIA - Burhani, Fadila Jzuqynova; Fariyanti, Anna; Jahroh, Siti (Forum Agribisnis, 2013)
Beef consumption needs of Indonesian  population tends to increase with the increasing number of the population and public awareness of the importance of animal protein. Meanwhile the price of beef and broiler meat are fluctuative. The value of volatility describes how much the level of risk that will be faced in the future. Fluctuations in the price of beef and broiler meat can be caused by  the unequilibrium of supply and demand.  The objectives of this research are (1) to identify the price volatility forecasting models of beef and broiler meat in Indonesia, (2) to identify factors that affect the price volatility of beef and broiler meat in Indonesia, and (3) to identify alternative strategies related to the price volatility of beef and broiler meat in Indonesia. This research used secondary data with the  time series form in the period of February 2003 to February 2013. In this research ARCH-GARCH was used to analyze the price volatility of beef and broiler meat in Indonesia. This analysis showed that the price volatility of beef and broiler meat in Indonesia would be smaller. Factors that affect the price volatility of beef in Indonesia are the price volatility of previous period and the price variance of the previous period. While the factors that affects the price volatility of broiler meat in Indonesia is the amount of price volatility in the previous period.